BOOSTING ENGLISH WRITING SKILLS: HOW GINGER SOFTWARE EMPOWERS LANGUAGE LEARNERS - Mansurudin, Mansurudin; Ilham, Ilham; Edi, Edi (Journal of English Education and Linguistics, 2025)
Writing skills are essential for learners in mastering English as a global language. Non-native learners face challenges such as grammatical errors, limited vocabulary, and lack of confidence, making technological solutions like Ginger Software highly relevant. This study employed a Systematic Literature Review (SLR) to analyze the effectiveness of Ginger Software in enhancing English writing skills. The research synthesizes findings from various studies published between 2015 and 2025, highlighting Ginger’s ability to improve grammar, vocabulary, and sentence structure through real-time feedback and context-based learning. Results indicate that Ginger Software significantly enhances writing quality, supports self-directed learning, and increases learners' motivation. However, challenges such as accessibility limitations, integration into workflows, and over-reliance on technology were also identified. While Ginger Software proves beneficial for addressing common writing errors, its limitations in providing nuanced, contextualized feedback emphasize the continued importance of educators in the learning process. This study concludes that combining AI-based tools like Ginger Software with traditional teaching methods can provide a balanced and comprehensive approach to improving English writing skills. Future research should explore strategies for greater inclusivity and the development of hybrid models integrating AI technologies with human instruction.